THE COSTS OF DEMOCRACY – HOW ELECTION-RELATED STRESS AFFECTS HEALTH - Beata Choromańska; Julia Procyk; Marta Danuta Cendrowska; Aleksandra Klukowska; Karolina Stępień; Justyna Berent; Paulina Rzepa; Barbara Ponitka; Julia Maszewska; Szymon Milnerowicz; Łukasz Brzost; Wiktoria Szumlińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Electoral campaigns represent significant sociopolitical stressors that may have notable implications for public health. The aim of this article is to present an in-depth overview of the documented health effects associated with election-related stress. Methods: PubMed was searched using keywords such as “sociopolitical stress” and “presidential election AND health”, applying a time filter 2016-2025. After removing duplicates, titles and abstracts were screened for relevance, and the most pertinent articles were included in this review. Results: Election periods were associated with increased psychological distress. Sociopolitical stress was related to higher incidence of depression, generalized anxiety disorder, sleep disturbances, cardiovascular and arrythmic events, elevated blood pressure, preterm births, heightened interest in long-acting reversible contraceptives, and altered birth sex ratio. These effects were particularly pronounced among supporters of the losing candidate, women, ethnic and racial minorities, and younger populations. Conclusion: These findings highlight the need for enhanced mental health support and public health preparedness during major political events.